IROKI Big Puzzle Learning Media to Improve Class IV Natural and Social Science Learning Outcomes - Nadya Putri Al-Fath; Deasylina Da Ary (Universitas Pendidikan Ganesha, 2026)
The limited integration of interactive media in science learning in elementary schools contributes to low student engagement and learning outcomes. This study aims to analyze the feasibility and evaluate the effectiveness of the IROKI Big Puzzle learning media in improving student learning outcomes. The study used a Research and Development (R&D) approach with the ADDIE model. The research subjects were 30 fourth-grade students who were designated as the experimental group. Data were collected through test techniques (pretest and posttest), questionnaire distribution for expert validation and user responses, and observation during the implementation of the learning. The research instruments included validation sheets from material experts and media experts, teacher and student response questionnaires, observation sheets, and cognitive learning outcome tests in the form of pretests and posttests. Data analysis was carried out using descriptive statistics, normality tests, paired t-tests, and N-Gain analysis. The results showed that the media had a high level of feasibility with a validation score of 92% from material experts and 93% from media experts. The average student score increased from 69.83 in the pretest to 92.50 in the posttest, with a significance value of 0.000 indicating a significant increase. The N-Gain score of 0.626 is in the moderate category, indicating meaningful learning improvement. It is concluded that the IROKI Big Puzzle is an effective learning innovation that contributes to the development of interactive media based on student-centered learning in elementary education and provides practical implications for improving the quality of thematic learning.